2020
DOI: 10.3389/fvets.2020.00443
|View full text |Cite
|
Sign up to set email alerts
|

Organic Selenium Ameliorates Staphylococcus aureus-Induced Mastitis in Rats by Inhibiting the Activation of NF-κB and MAPK Signaling Pathways

Abstract: Mastitis is an economically important disease in dairy cows, which is often caused by Staphylococcus aureus ( S. aureus ). Selenium is an indispensable element for physiological function and contributes to reduce injury of the mammary glands in mastitis. However, adequate sources of selenium have always been an important consideration for livestock. Therefore, the study aimed to explore the protective effect and mechanism of Selenohomolanthionine (SeHLan) on mastit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Additionally, it has been observed that supplementation of dairy cattle with Se inhibits the growth of S. aureus in bovine milk, in comparison with control cows [ 67 ]. Similarly, a recent in vivo study has demonstrated that organic Se ameliorates S. aureus induced mastitis in rats [ 68 ]. Still, it is more likely that selenium modulates Staphylococcus levels indirectly.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been observed that supplementation of dairy cattle with Se inhibits the growth of S. aureus in bovine milk, in comparison with control cows [ 67 ]. Similarly, a recent in vivo study has demonstrated that organic Se ameliorates S. aureus induced mastitis in rats [ 68 ]. Still, it is more likely that selenium modulates Staphylococcus levels indirectly.…”
Section: Resultsmentioning
confidence: 99%
“…Liu, Ding, et al. (2020) disclosed that organic Se supplementation protected the mammary glands from S . aureus injury by regulating various disturbances along with MAPKs (Liu, Ding, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2020) disclosed that organic Se supplementation protected the mammary glands from S . aureus injury by regulating various disturbances along with MAPKs (Liu, Ding, et al., 2020). This study indicates that Se as an antioxidant performs a crucial role in suppressing the apoptosis of normal spermatogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Serum resistance assay was performed in a 96-well plate as described previously [ 27 ]. Briefly, specific-pathogen-free (SPF) mouse serum was diluted to 50% with PBS.…”
Section: Methodsmentioning
confidence: 99%